Diversity and metabolic potentials of microbial communities associated with pollinator and cheater fig wasps in fig-fig wasp mutualism system - Dong, Yiyi; Zhang, Zheng-Ren; Mishra, Sandhya; Wong, Adam Chun-Nin; Huang, Jian-Feng; Wang, Bo; Peng, Yan-Qiong; Gao, Jie (Frontiers in Microbiology, 2022)
Microbial symbionts can influence a myriad of insect behavioral and physiological traits. However, how microbial communities may shape or be shaped by insect interactions with plants and neighboring species remains underexplored. The fig-fig wasp mutualism system offers a unique model to study the roles of microbiome in the interactions between the plants and co-habiting insects because a confined fig environment is shared by two fig wasp species, the pollinator wasp (Eupristina altissima and Eupristina verticillata) and the cheater wasp (Eupristina sp1 and Eupristina sp2). Here, we performed whole genome resequencing (WGS) on 48 individual fig wasps (Eupristina spp.) from Yunnan, China, to reveal the phylogenetic relationship and genetic divergence between pollinator and congeneric cheater wasps associated with the Ficus trees. We then extracted metagenomic sequences to explore the compositions, network structures, and functional capabilities of microbial communities associated with these wasps. We found that the cheaters and pollinators from the same fig species are sister species, which are highly genetically divergent. Fig wasps harbor diverse but stable microbial communities. Fig species dominate over the fig wasp genotype in shaping the bacterial and fungal communities. Variation in microbial communities may be partially explained by the filtering effect from fig and phylogeny of fig wasps. It is worth noting that cheaters have similar microbial communities to their sister pollinators, which may allow cheaters to coexist and gain resources from the same fig species. In terms of metabolic capabilities, some bacteria such as Desulfovibrio and Lachnospiraceae are candidates involved in the nutritional uptake of fig wasps. Our results provide novel insights into how microbiome community and metabolic functions may couple with the fig-wasp mutualistic systems.